2002
DOI: 10.1016/s1472-6483(10)61594-5
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of cellular fragments in a human embryo: time-lapse recordings

Abstract: An observation is reported of internalization of a cellular fragment into a blastomere from a human embryo, as documented by time-lapse photography. The fragment, created during the first mitotic cleavage was reabsorbed into one of the mother blastomeres in less than 5 min. The time-lapse sequence, shown here as a series of still photographs, provides the first direct evidence that cellular fragments in human embryos can 'disappear' during the culture period, a phenomenon that is common in human IVF. The time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 3 publications
2
53
1
Order By: Relevance
“…There is a well-documented correlation between embryo morphology evaluated at certain time-points and embryo competence as reviewed in a recent consensus paper by ALPHA and ESHRE [16]. However, the progressive and dynamic nature of cell cleavage and embryo development is also well known [13,18,30], and embryo scoring can change markedly within few hours [25]. In conventional morphological evaluation of embryo quality the number and duration of inspections outside the incubator must be restricted since changes in environment are known to induce stress [42].…”
Section: Discussionmentioning
confidence: 99%
“…There is a well-documented correlation between embryo morphology evaluated at certain time-points and embryo competence as reviewed in a recent consensus paper by ALPHA and ESHRE [16]. However, the progressive and dynamic nature of cell cleavage and embryo development is also well known [13,18,30], and embryo scoring can change markedly within few hours [25]. In conventional morphological evaluation of embryo quality the number and duration of inspections outside the incubator must be restricted since changes in environment are known to induce stress [42].…”
Section: Discussionmentioning
confidence: 99%
“…The target was to explore the dynamics of an embryo to implant successfully along with its various cleavage patterns and characteristics, by observing it at various stages of development [12,[15][16][17][18][19][20][21]. Recent studies reported information on the association of the type of fertilization [22], the IVF protocol used [23], female obesity [24], and smoking [25] on embryo kinetics and development.…”
Section: Introductionmentioning
confidence: 99%
“…The first clinically relevant application of TLS for use in the embryology laboratory was reported in 1994 where the events of fertilisation were studied using a custom-made imaging system comprising a microscope, enabled with Nomarski DIC optics, a video recorder and a switching box (Inoué and Inoué, 1994). Regarding preimplantation embryonic development, the first report of internalisation of fragments was published (Hardarson et al., 2002) followed by a report of mouse embryo collapse analysed using time-lapse photography (Niimura, 2003). Focus turned to the use of TLS in a clinical setting, quite abruptly, in 2008 with a number of publications exclusively studying preimplantation embryonic development using TLS and how the information these systems provided could be used to determine embryo viability (Arav et al, 2008;Lemmen, Agerholm, Ziebe, 2008;Mio and Maeda, 2008).…”
mentioning
confidence: 99%